PENGOLAHAN ARSIP INAKTIF DI PUSAT STUDI KEBUDAYAAN UGM YOGYAKARTA - , KEN WESTI N.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final report is describe about the arrangement of inactive records in Center For Cultural Studies (PSK UGM). The final report is describe about the inactive records condition, arrangement of inactive records, facilities and infrastructure which is needed, and the obstacles encountered in the arrangement of inactive records in PSK UGM. The purpose of this report is to expand our field knowledge field of archives and trained to implement the arrangement of inactive records. There are three methods were used to collect data. First method is participant-observation. Participant-observation used to collecting the information which taken by direct observation. Second method is interview. This method used to get information directly from officers on the ground. The last method is study literature. The purpose of this method is collecting data from various sources of literature that relevant to final report. The conclusion of the final report is the condition of the inactive record in PSK UGM is not organized so that it is needed repairing and arrangement. It is because the limited of human resources PSK UGM so that the handling of inactive records is not optimal. Suggestions to support the improvement of the arrangement is to provide facilities and infrastructure in accordance with standard archival and human resources specifically responsible for implementing the management of inactive records.